Service innovation affecting customer satisfaction and customer loyalty toward services provided by event organizing companies in Thailand - Suntornwipart, Pachara; Bandurat, Patipan; Vuthisopon, Sujira (Edelweiss Applied Science and Technology, 2025)
This study aimed to (1) assess the levels of service innovation, service quality, customer satisfaction, and customer loyalty among clients of event organizing companies in Thailand, and (2) examine the influence of these factors on customer loyalty. A quantitative approach was employed using a structured questionnaire with a five-point Likert scale. The sample consisted of 340 respondents, and the questionnaire had a high reliability coefficient (α = 0.96). Data analysis was conducted using SPSS for descriptive statistics and LISREL for confirmatory factor analysis and structural equation modeling. Findings revealed that the levels of service innovation, service quality, customer satisfaction, and customer loyalty were all rated at a high level. The structural equation model showed an excellent fit with empirical data (Chi-Square = 69.54, df = 110, p = 0.99, χ²/df = 0.63, RMSEA = 0.00, RMR = 0.00, CFI = 0.99, GFI = 0.99, AGFI = 0.99). The model explained 74% of the variance in customer loyalty. Service innovation had the highest total effect (0.97), followed by service quality (0.82), and customer satisfaction (0.32), indicating that all three factors significantly influenced customer loyalty directly and/or indirectly. Customer loyalty in Thailand’s event management industry is strongly influenced by service innovation, quality, and satisfaction. Among these, service innovation is the most critical determinant. The validated model provides a strategic framework for event organizers to enhance service delivery. Focusing on innovation and quality improvements can strengthen customer loyalty, support strategic planning, and offer a competitive edge in Thailand’s event management sector.